Eyebrow Position After Paramedian Forehead Flap Nasal Reconstruction - Yalamanchali, Sreeya (JAMA Facial Plast Surg, 2018)
This study compared preoperative and postoperative photographs of patients who underwent nasal reconstruction with paramedian forehead flaps to analyze differences in eyebrow position.